On morphic modules over commutative rings - TEKİR, ÜNSAL (My University, 2022)
A commutative ring R is said to be a morphic ring if for each a ∈ R there exists b ∈ R such that ann(a) = Rb and ann(b) = Ra. In this paper, we extend the notion of morphic rings to modules and we study the introduced concept by comparing it with some related notions
Keywords: Comorphic ring; Comorphic module